The Role of Education in Socialization and the Formation of Social Values The Process of Internalizing Values Norms and Culture Through Formal and Non-Formal Education - Izzuddin, Moh; Mulyana, Asep; Analismy, Suuci; Sopiulloh, Wafa (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Education plays a crucial role in shaping students' social values through an ongoing socialization process. Values, norms, and culture are imparted not only through formal education at school but also through non-formal education that occurs at home and in the community. This article aims to explore the role of formal and non-formal education in the process of internalizing social values and to identify unresolved research gaps in education and the sociology of education. The method used is a literature review, analyzing relevant books and journal articles. The results indicate that formal education emphasizes knowledge and rules, while non-formal education is more closely linked to social experiences and real-world contexts. However, there are still limitations in research that comprehensively integrates both types of education within the context of social change and digitalization.